PELAKSANAAN PROMOSI PADA PT. MITRA MEGAH PROFITAMAS CABANG TANJUNG - Widarto Widarto; Muhammad Ary Saputra (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2019)
The purpose of this research is to know the implementation of the promotion, to know the constraints faced and to know the efforts made by the company to overcome the constraints faced. The method of study used is a descriptive method. As for Key informant or key informant is the operational manager and the helper informant is the Branc manager. The techniques used in data collection are: interviews, documentation and observation. The data analysis technique that researchers use is qualitative analysis. The results showed that: the promotion implementation of PT. Megah Profitamas is conducted through advertising (advertising), personal Selling, sales promotion, PR (publicity) and direct marketing ( Direct Marketing), the obstacles faced by PT. Mitra Megah Profitamas In its promotional activities are: In general, support or funding from the center is still very minimal, especially for advertising and sales promotion activities, other activities Personal selling and publicity is still not optimal, while the efforts made by PT. Mitra Megah Profitamas related constraints encountered in the implementation of the promotion is to utilize as much as possible advertising activities through Radio good Smart FM J Radio. The selection of time and the broadcast period is selected and adjusted to the existing financial condition, even if it is necessary for the frequency to be selected in certain months. Similarly, the sales promotion is syndidate with the activities of local government, private and community, for publicity improves cooperation on various parties and trains the ability of employees to have the ability to release news from Company activities. It is advisable that advertising efforts through local television or radio media and personal selling activities need to be done directly with the potential companies in the form of MOU so that each visit made by PT. Mitra Megah Profitamas Already well-programmatic. For sales promotion and publicity is synching to the activities or the District agenda and private agenda, so the cost is lower.